Design and fabrication of egg washing machine / Mohamed Adli Mohamed Yusof - Mohamed Yusof, Mohamed Adli (2023)
Chicken and other egg laying creatures are kept widely throughout the world and mass production of chicken eggs is a global industry. During production, eggs are usually candied to check their quality. Some restaurant businesses still wash eggs using the old method which is by washing the eggs individually using a sponge. The main problem with this method is that it is time-consuming and the quantity of eggs that can be washed per day is not in mass. The eggs will be cleaned inconsistently because manpower is not as efficient as a machine. Therefore, the aim of this project is to design and fabricate an egg washing machine at an affordable price. This idea is developed in the hope of cleaning eggs without using a lot of manpower, but economical as well